Austerity, Community Action, and the Future of Citizenship in Europe (Book collections on Project MUSE., 2018)
"The politics of autherity has seen governments across Europe cut back on welfare provision. As the state retreats, this edited collection explores secular and faith-based grassroots social action in Germany and the United Kingdom that has evolved in response to changing economic policy and expanding needs, from basic items such as food to more complex means to move out of poverty. Bringing together scholars from different disciplines and practitioners in several areas of social intervention, the book explores how practices of citizenship and community are changing because of the retreat of the state. The book analyses how the challenges of meeting social and material needs create new opportunities for local activism."